Impact of fishing crafts and fisheries harbours in marine fish production in Sri lanka - Sivaraja, S.; Sooriyakumar, K.; Sarujan, S. (University of Jaffna, 2017)
The fisheries sector plays a vital role with respect to provision of direct and indirect employment opportunities, generation of income, and provision of reasonably priced protein for the rural and urban masses in the country. Importation of fish and fishery products shows increasing trend in recent years. This leads to a decrease in the foreign exchange reserve. Sri Lankan policy makers should formulate better policy to increase domestic fish production. This paper examines the impact of the fishing crafts and fisheries harbour in marine fish production in Sri Lanka. For this study, secondary time series data for the variables mentioned above were collected from 2001 to 2015. Augmented Dickey Fuller Test (ADF) was used to test whether these data are stationary or non-stationary. After checking the stationary of time series data, cointegration regression models for annual deep sea fish production and annual coastal fish production were developed by using fully modified Ordinary Least Square (OLS) method. Panel regression models for marine fish production at provincial levels were developed. These results clearly indicated that number of fishing boats and number of harbours significantly contributes to the marine fish production. The results of this study would be useful to the policy makers to develop the policies to increase domestic production.
Keywords: Augmented dickey fuller test; Cointegration regression model; Marine fish production; Panel regression model